2023
DOI: 10.1149/1945-7111/ad0e44
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Effects of Temperature on Nonaqueous Redox Flow Cell Cycling Performance

Alexander H. Quinn,
Katelyn M. Ripley,
Nicholas J. Matteucci
et al.

Abstract: The impact of cell temperature is a relatively underexplored area within the burgeoning field of nonaqueous redox flow batteries (NAqRFBs). Here, we investigate the effect of elevated temperature on the performance of nonaqueous redox electrolytes and associated flow cells. Using a model compound, N-(2-(2-methoxyethoxy)-ethyl)phenothiazine (MEEPT), in a propylene-carbonate-based electrolyte, we experimentally measure the temperature dependence of relevant physicochemical properties (i.e., electrolyte conductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 86 publications
(115 reference statements)
0
7
0
Order By: Relevance
“…Additionally, in the study by Quinn et al , the thermal stability of N -(2-(2-methoxyethoxy)-ethyl)phenothiazine (MEEPT) material was assessed in a non-aqueous electrolyte, applying a decently accurate heating setup (Table S1†) and performing in the 30 to 70 °C temperature range with 10 °C increments. 24 Unfortunately, capacity fade values were not stated for the performed symmetric cycling and, thus, we have extracted the values from the figure five in the corresponding publication by converting the figure into data points using the WebPlotDigitizer program. 56 The obtained charge capacity from time dependency is depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, in the study by Quinn et al , the thermal stability of N -(2-(2-methoxyethoxy)-ethyl)phenothiazine (MEEPT) material was assessed in a non-aqueous electrolyte, applying a decently accurate heating setup (Table S1†) and performing in the 30 to 70 °C temperature range with 10 °C increments. 24 Unfortunately, capacity fade values were not stated for the performed symmetric cycling and, thus, we have extracted the values from the figure five in the corresponding publication by converting the figure into data points using the WebPlotDigitizer program. 56 The obtained charge capacity from time dependency is depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the scarcity of the thermal stability evaluations of organic cathode materials, the obtained capacity fade rates of the newly emerged MEEPT study are valuable for providing an idea about the current state of the reported results. Nevertheless, we emphasize that the stated values represent a rough estimation, obtained by digitizing the graph from the work of Quinn et al 24 Hence, firstly, the capacity fades calculated from the original values may differ. Secondly, even if the digitalization of the figure was accurate, the statements on the fade rate behavior, which are based on such short battery tests, are of low reliability.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Symmetric cells with only one heated reservoir were used to cycle aqueous TEMPO-based RAOMS, however no statistical difference in temporal capacity fade rates at room temperature vs 40°C was observed. 45,46 Quinn & Ripley et al 47 investigated the effect of elevated temperature on the physicochemical and electrochemical properties, and RFB performance, of nonaqueous RAOMs up to 70°C. Many of the temperature effects explored in Ref.…”
mentioning
confidence: 99%